Dear British criminology: Where has all the race and racism gone?. (August 2020) - Phillips, Coretta; Earle, Rod; Parmar, Alpa; Smith, Daniel
In this article we use Emirbayer and Desmond's institutional reflexivity framework to critically examine the production of racial knowledge in British criminology. Identifying weakness, neglect and marginalization in theorizing race and racism, we focus principally on the disciplinary unconscious element of their three-tier framework, identifying and interrogating aspects of criminology's 'obligatory problematics', 'habits of thought' and 'position-taking' as well as its institutional structure and social relations that combine to render the discipline 'institutionally white'. We also consider, briefly, aspects of criminology's relationship to race, racism and whiteness in the USA. The final part of the article makes the case for British criminology to engage in telling and narrating racisms, urging it to understand the complexities of race in our subject matter, avoid its reduction to class and inequality, and to pay particular attention to reflexivity, history, sociology and language, turning to face race with postcolonial tools and resolve.